Pelaksanaan Pembelajaran Seni Tari pada Kurikulum Merdeka Belajar di SMA Negeri 2 Bayang - Rena Petmita; Susmiarti Susmiarti (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2024)
This study aims to find out and describe the Implementation of Dance Art Learning in the Independent Curriculum in Class X.E4 SMA Negeri 2 Bayang. The type of research used in this study is qualitative research with a descriptive approach. The research instrument is the researcher himself and assisted by other instruments such as stationery and mobile phones. Data collection techniques include observation, interviews, literature studies and documentation. The steps in analyzing data are data collection, data reduction, classifying and concluding data. The results of the study show that the implementation of dance learning in the independent curriculum at SMA Negeri 2 Bayang has not been carried out properly, where there are several things in its implementation that are not in accordance with the teaching module so that the implementation is less effective. In terms of the learning methods used, teachers have used methods that are in accordance with the material. However, when teachers carry out training with material on functions, meanings and symbols through a variety of local dance movements, teachers have not used media in learning, such as the use of audiovisual media that can affect student learning outcomes.